Interface crack kinking in composites materials - Chong, Yeong Sen (2018)
Composites are often exposed to severe loading conditions which later may lead to crack formation and propagation. The interface crack is explored in this study by employ the hypothesis of linear elastic fracture mechanics and finite element methods. By alter the De-Bonding Angle and Young’s Modulus to ratify the impact to Stress Intensity Factors and validity of the two-phase modelling. The study also comprises the expansion of two-phase modelling and can be clarifies and accomplishes the interface crack kinking in composites material. Additionally, the stress intensity factors around the crack tip and crack propagation can also be calculated by two-phase model.